2016
DOI: 10.1002/jso.24314
|View full text |Cite
|
Sign up to set email alerts
|

Defining the optimal timing of adjuvant therapy for resected pancreatic adenocarcinoma: A statewide cancer registry analysis

Abstract: In this statewide analysis, there was no difference in OS between early and late AT initiation for resected PDAC. The ideal window for AT initiation remains unknown as tumor biology continues to trump regimens from the past decade. J. Surg. Oncol. 2016;114:451-455. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
11
1
1
Order By: Relevance
“…These 34 studies corresponded to the post-hoc analyses of randomized controlled trials and cohorts and to retrospective studies. They included a total of 141,853 patients: 134,701 in the colon cancer cohort, as shown in Table 1 [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]; 5121 in the gastric cancer cohort, as shown in Table 2 [26,27,28,29,30,31]; and 2031 in the pancreatic cancer cohort, as shown in Table 3 [32,33,34,35,36,37]. Among these studies, 22 were used for the colorectal cancer analysis and six were used for pancreatic and gastric cancer each.…”
Section: Resultsmentioning
confidence: 99%
“…These 34 studies corresponded to the post-hoc analyses of randomized controlled trials and cohorts and to retrospective studies. They included a total of 141,853 patients: 134,701 in the colon cancer cohort, as shown in Table 1 [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]; 5121 in the gastric cancer cohort, as shown in Table 2 [26,27,28,29,30,31]; and 2031 in the pancreatic cancer cohort, as shown in Table 3 [32,33,34,35,36,37]. Among these studies, 22 were used for the colorectal cancer analysis and six were used for pancreatic and gastric cancer each.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies suggested no benefit to early initiation of adjuvant therapy but only compared survival between arbitrarily assigned time periods. 15,16,17,18,19…”
Section: Introductionmentioning
confidence: 99%
“…Two additional reports from 2016 found no differences in OS when comparing those who started chemotherapy within 8 weeks of surgery and those who started treatment after the eight‐week timepoint. 14 , 15 Lee et al 17 reported that early vs late initiation of adjuvant therapy, defined as before or after 6 weeks postoperatively, did not impact OS. However, the authors also commented that patients who were able to complete therapy had a significant survival advantage.…”
Section: Discussionmentioning
confidence: 99%
“…10 Indeed, the time from a patients' operation until starting adjuvant therapy can vary widely. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 Some patients may never recover enough to receive any amount of adjuvant treatment. Alternatively, patients may not tolerate multi‐agent chemotherapy after resection and instead receive less effective single agent therapy.…”
Section: Introductionmentioning
confidence: 99%